ПРАВОПОРУШЕННЯ У СФЕРІ ЕКОНОМІКИ ЯК ЧИННИК ЗАГРОЗИ РИНКОВИМ ВІДНОСИНАМ У ДЕРЖАВІ - Кантор, Наталія Юріївна (SUPREMANCE OF LAW, 2018)
The article is devoted to the study of issues of prevention of offenses in the field of economics, which poses a real threat to market relations in Ukraine. It is indicated that the current normative base and law-enforcement practice in the field of prevention of offenses in the field of economics are constantly updated and require a theoretical understanding given that: firstly, in the doctrine of administrative law, there was no holistic understanding of the mechanism of prevention of offenses in a specific sphere of social relations - economic activity in the conditions of the transformational processes of modern society; secondly, for a long time the idea of the meaning and content of prevention of administrative offenses in the economic sphere was simplified and included only a set of preventive means and methods without taking into account the specifics of certain spheres of the market economy, the specifics of economic entities, the significant increase in the diversity and complexity of their operations, modern realities of development of the state and civil society, integration of the domestic economy into European and world space.